Pengaruh Media Flipbook Digital sebagai Inovasi Pembelajaran terhadap Minat Belajar Peserta Didik - Hasanudin Kasim; Jalal Jalal; Arfenti Amir; Muh. Reski Salemuddin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aimed to: (1) examine the implementation of flipbook-based instructional media in Social Studies learning at Amanah Nusantara Junior High School; (2) describe students’ learning interest when using flipbook media in Social Studies instruction; and (3) analyze the effectiveness of flipbook-based learning in enhancing students’ learning interest. The study employed an experimental approach using a pre-experimental design, specifically a one-group pretest–posttest design. Data analysis procedures included prerequisite tests (normality and homogeneity tests), paired sample t-test, linearity test, and simple linear regression analysis. The findings revealed that the use of flipbook instructional media was effective in improving students’ learning interest, as indicated by a significant increase in mean scores from the pretest (70.37) to the posttest (76.23). Statistical analysis further demonstrated a strong and significant linear relationship between the use of flipbook media and students’ learning interest, with a contribution value of 65% and a strong correlation coefficient (R = 0.806). The paired t-test results confirmed a significant difference between pretest and posttest scores, with a calculated t-value of −10.956 exceeding the critical t-value of 2.045 (absolute value), indicating a meaningful effect of flipbook media on students’ learning interest. Moreover, the F-test result (F = 51.939; p = 0.000) indicated that the regression model was statistically feasible for predicting learning interest. Overall, the findings confirm that flipbook-based instructional media exert a significant influence on enhancing students’ learning interest in Social Studies learning.